The Role of Blue Ocean Strategy In Filling the Knowing-doing Gap in Public Organizations «Proposed Vision» - Mohamed , Abdelrahim (The Arab Journal of Administration, 2021)
Nowadays the organizations are working in fluctuated and rapid environment, these changes created the competition in the public and private organizations to keep his role in the market and achieve the customer satisfaction. These changes encourage for appearing the blue ocean strategy, that focuses on avoiding the competition and working to innovate the value. The problem of the research focused on how to apply the blue ocean strategy in public organizations to fill the knowing-doing gap. The importance of the research concentered on the blue ocean strategy and its role in creative thinking and thinking out the box to introduce products and services. In addition, the importance of the research focus on the application of the key corners, reduce, eliminate, rise and innovate and how to fill the execution gap. The research tends to formulate proposed vision, how to build the blue ocean strategy in public organizations. This research concluded that the blue ocean strategy can playing important role in case of applying it in public organizations. the research recommended for applying the proposed vision that mentioned in this research under title “proposed vision for applying the blue ocean strategy in public organizations.